2015
DOI: 10.1586/1744666x.2015.1060857
|View full text |Cite
|
Sign up to set email alerts
|

The histiocytosis Erdheim–Chester disease is an inflammatory myeloid neoplasm

Abstract: Erdheim-Chester disease (ECD) is a rare, non-Langerhans histiocytosis, characterized by the infiltration of tissues by foamy CD68(+)CD1a(-) histiocytes. (99)Technetium bone scintigraphy revealing almost constant tracer uptake by the long bones is highly suggestive of ECD, and a 'hairy kidney' appearance on abdominal computed tomography scan is observed in about half of all ECD cases. CNS involvement is a strong prognostic factor and independent predictor of death. IFN-α seems to be the best initial treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 65 publications
1
33
0
1
Order By: Relevance
“…Clinical, imaging, and molecular data were analyzed using descriptive statistics, and BRAF versus atrophy comparisons were performed using a one‐tailed Fisher’s exact test. A one‐tailed test was used because the BRAF V600E variant is likely pathogenic and correlates with worse organ‐specific disease in untreated patients . Diffusion tensor imaging and volumetric data were compared using the FSL Randomise tool (v5.0.11, 5000 permutations) – which conducts pairwise, permutation‐based inference on t ‐statistic maps – was used to identify clusters of voxels that differed between the healthy controls and patient group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical, imaging, and molecular data were analyzed using descriptive statistics, and BRAF versus atrophy comparisons were performed using a one‐tailed Fisher’s exact test. A one‐tailed test was used because the BRAF V600E variant is likely pathogenic and correlates with worse organ‐specific disease in untreated patients . Diffusion tensor imaging and volumetric data were compared using the FSL Randomise tool (v5.0.11, 5000 permutations) – which conducts pairwise, permutation‐based inference on t ‐statistic maps – was used to identify clusters of voxels that differed between the healthy controls and patient group.…”
Section: Methodsmentioning
confidence: 99%
“…Erdheim–Chester disease (ECD) is a treatable histiocytic neoplasm frequently involving the brain. It is characterized by infiltration and accumulation of inflammatory foamy macrophages in multiple tissues leading to end‐organ dysfunction and failure through mass effect, tissue restriction, organ encasement, and by local and systemic inflammatory cytokines . The most commonly involved organs are bone, retroperitoneum, kidneys, brain, heart, skin, and lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Mutasjoner i BRAF-V600E (16,17), NRAS og PIK3CA (18), som alle er protoonkogener involvert i karsinogenesen av flere kreftformer, kan vaere viktige. Det indikerer at sykdommen muligens representerer en malign tilstand (19). Det har også vaert diskutert om immunmedierte mekanismer, cytokiner og kjemokiner kan føre til akkumulering av histiocytter i de affiserte vevene og at det indikerer at en inflammatorisk komponent er involvert i utviklingen av sykdommen (20)(21)(22).…”
Section: Diskusjonunclassified
“…In small case series, interferon-α has resulted in variable recovery [6]. A recent report [8] describes 2 patients with Erdheim-Chester disease (ECD), a form of NLH, treated with the recombinant interleukin (IL)-1 receptor antagonist anakinra, which induced significant or complete resolution of this inflammatory myeloid neoplasm [9]. It is suggested that the anti-inflammatory effect of anakinra on macrophages would account for the improvement in the proliferation of these cells in different areas.…”
Section: Introductionmentioning
confidence: 99%